Implementasi Pembelajaran Inklusif dengan Menggunakan Media Gambar bagi Anak ADHD di SDN Kemuning Tarik Sidoarjo - Amelia Putri, Arnetta; Nova Estu Harsiwi (Universitas Palangka Raya, 2025)
Inclusive education is an education system that is friendly to all individuals without distinguishing the diversity of their characteristics. This system provides educational services that allow children with special needs to learn with their peers in the public school closest to where they live. This study aims to examine the